Pengaruh Penggunaan Sistem Enterprise Resource Planning dan Kualitas Audit terhadap Kinerja Laporan Keuangan di Perusahaan Jasa di Jakarta - Judijanto, Loso (Sanskara Akuntansi dan Keuangan, 2024)
This study examines the influence of Enterprise Resource Planning (ERP) system usage and audit quality on financial reporting performance in service companies in Jakarta. Using a quantitative approach, data were collected from 36 service companies through structured questionnaires and analyzed using SPSS version 26. The results show that both ERP system usage and audit quality have a significant positive effect on financial reporting performance. Specifically, higher levels of ERP system integration and robust audit practices enhance the accuracy and reliability of financial reporting. Additionally, the interaction between ERP system usage and audit quality further strengthens these benefits. These findings underscore the importance of implementing comprehensive ERP solutions and maintaining high audit standards to improve financial performance in the service sector.